Skeletal and Dentoalveolar changes concurrent to use of Twin Block appliance in Class II division I cases with a deficient mandible: A cephalometric study - A K Sharma; V Sachdev; A Singla; B C Kirtaniya (Wolters Kluwer Medknow Publications, 2012)
Most of Class II malocclusions are due to underdeveloped mandible with increased overjet and overbite. Lack of incisal contact results in the extrusion of the upper and lower anterior dentoalveolar complex, which helps to lock the mandible and prevent its normal growth and development, and this abnormality, is exaggerated by soft tissue imbalance. The purpose of present study was to cephalometrically evaluate skeletal and dentoalveolar changes following the use of Twin-Block appliance in 10 growing children of age group 9-13 years (mean 11.1 year ± SD 1.37) of Class II division 1 malocclusion with a deficient mandible. Cephalometric pre- and post-functional treatment measurements (angular and linear) were done and statistically analyzed using student's paired t-test. The results of the present study showed that maxilla (SNA) was restricted sagittally (head gear effect) with marked maxillary dental retraction. Significant mandible sagittal advancement (SNB) with minimum dental protraction was observed with significant increase in the mandibular length. The maxillomandibular skeletal relation (ANB and WITS appraisal) reduced considerably which improved the profile and facial esthetics. Pronounced correction of overjet and overbite was seen. The present study concluded that Class II correction occurs by both skeletal and dentoalveolar changes.